Exploring Self-Disclosure and Its Impact on Psychological Well-Being among Homosexuals (Gay) - Prabandari, Ruby Bulan; Huwae, Arthur (Bulletin of Counseling and Psychotherapy, 2024)
Progress over time has encouraged the gay community to be more open about their sexual identity. However, there is still stigma and societal disacceptance because they are considered deviant from religion, law and culture. This research aims to determine the relationship between self-disclosure and the psychological well-being of homosexuals (gay) in Central Java. The method used is quantitative with a correlational design. A total of 237 homosexuals (gay) in Central Java were used as research participants using incidental sampling techniques. Research measurements used the Revised Self-Disclosure Scale (α = .92) and the Ryff Psychological Well-Being Scale (α = .543-.828). The research data analysis method uses the product-moment correlation test from Karl Pearson. The research results show a significant, but not strong, positive relationship between self-disclosure and psychological well-being (r = .147 and sig. = .012). This indicates that self-disclosure is one of the factors related to increasing the psychological well-being of homosexuals (gays) in Central Java. The implication of this research is the need for self-disclosure for homosexuals (Gay) to vent all the feelings and inner pressure they experience and make them feel more relieved to improve their psychological well-being to live their lives well for the sake of past goals. Future research should be able to develop research by looking for other factors related to self-disclosure and psychological well-being.